Comparison of a Point-of-Care Analyzer With a Chemiluminescent Immunoassay for Serum Progesterone Measurement in Breeding Management of the Bitch - Zuercher, Julia; Boes, Katie M.; Balogh, Orsolya; Helms, Alyssa B.; Cecere, Julie T. (Frontiers in Veterinary Science, 2021)
Accurate serum progesterone measurements for timing bitches during breeding management is critical for reproductive practice, especially as artificial insemination has become routine to facilitate breeding of animals that are geographically or temporally separated. To measure serum progesterone, chemiluminescent immunoassay (CLIA) has replaced radioimmunoassay as the current standard in the bitch due to its high correlation and increased practicality. In January 2019, a colorimetric point-of-care (POC) immunoassay for quantitative in-clinic canine serum progesterone measurements in <30 min was released. This study provides an independent comparison of the POC (Catalyst One, IDEXX) to the current industry standard, CLIA (Immulite-2000, Siemens). To assess inter-assay imprecision of POC and agreement of the POC and CLIA results, 100 canine serum samples were analyzed on three analyzers (POC-1, POC-2, and CLIA), of which, 74 (POC-1) and 75 (POC-2) results were within POCs' reportable range of 0.2–20 ng/mL and included in the study. To assess intra-assay imprecision, pooled canine serum samples at low (L1), intermediate (L2), and high (L3) progesterone concentrations were analyzed ten times each on POC-1 and CLIA. Relative to CLIA, POC values showed good correlation (POC-1, r2 = 0.9366; POC-2, r2 = 0.9438, P < 0.0001) and significant positive proportional bias at values >2 ng/mL. The POC inter-assay coefficients of variation (CVs) were 13.2% (0.2–2.9 ng/mL, 0.6–9.2 nmol/L, L1), 10.0% (3.0–9.9 ng/mL, 9.5–31.5 nmol/L, L2), 7.1% (10.0–20.0 ng/mL, 31.8–63.6 nmol/L, L3), and 11.2% (all samples). The intra-assay CVs for POC (L1, 15.3%; L2, 7.0%; L3, 4.7%) were higher than those for CLIA (L1, 5.89%; L2, 4.89%; L3, 3.44%). Based on the more rapid increase in serial serum progesterone concentrations in ovulating bitches and the greater imprecision of the POC, the clinical interpretations of serum progesterone measurements as they relate to canine breeding management should be made with caution.